2015
DOI: 10.1039/c4cp04172k
|View full text |Cite
|
Sign up to set email alerts
|

Highly chromium contaminant tolerant BaO infiltrated La0.6Sr0.4Co0.2Fe0.8O3−δ cathodes for solid oxide fuel cells

Abstract: A BaO infiltrated La0.6Sr0.4Co0.2Fe0.8O3-δ (LSCF) cathode shows remarkable tolerance and resistance towards chromium via the formation of BaCrO4 instead of SrCrO4 on the electrode surface, preventing the excess Sr deficiency at the A-site of LSCF perovskite and thus mitigating the Cr poisoning effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
36
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 62 publications
(41 citation statements)
references
References 27 publications
3
36
0
Order By: Relevance
“…This is in general consistent with the reported formation of BaCrO 4 , CoCr 2 O 4 , CrNdO 3 , and Cr 2 O 3 phases after the heat-treatment of NdBaCo 2 O 5+d electrode in contact with Cr pellet at 800 C for 2h [17]. The formation of less conductive phases like BaCrO 4 [21] and the decomposition of SBCO are detrimental to the electrochemical activity of SBCO cathode, as evidenced by the significant increase in both h and R p (Fig 1).…”
Section: Methodssupporting
confidence: 90%
“…This is in general consistent with the reported formation of BaCrO 4 , CoCr 2 O 4 , CrNdO 3 , and Cr 2 O 3 phases after the heat-treatment of NdBaCo 2 O 5+d electrode in contact with Cr pellet at 800 C for 2h [17]. The formation of less conductive phases like BaCrO 4 [21] and the decomposition of SBCO are detrimental to the electrochemical activity of SBCO cathode, as evidenced by the significant increase in both h and R p (Fig 1).…”
Section: Methodssupporting
confidence: 90%
“…Instead of SrCrO 4 , BaCrO 4 phase is detected. BaCrO 4 is reported to be more stable compared to SrCrO 4 [33]. Therefore, the Cr deposition (CrO 3 , Cr 2 O 3 ) on the BSCF takes place by interacting with Ba 2+ rather than with Sr 2+ with the presence of BaO.…”
Section: Microstructuresmentioning
confidence: 93%
“…Our previous work has also demonstrated that these large particles are SrCrO 4 and they mainly reside on the surface of the cathode [31,32]. The formation of the poorly conductive SrCrO 4 (1.8 Â 10 À5 and 1.8 Â 10 À4 SÁcm À1 at 700 C and 800 C respectively [33]) increases the electrode ohmic resistance by blocking the electrical conductivity path. Also, SrCrO 4 formation extracts Sr species from the LSCF lattice, leading to Sr deficiency at the A-site.…”
Section: Microstructuresmentioning
confidence: 95%
See 1 more Smart Citation
“…No SrCrO 4 peaks are detected and the SSCF cathode is stable after 100 hrs of the thermal treatment.This further proves that the Co 0.8 Fe 0.2 oxide coating is effective in inhibiting the Cr diffusion and evaporation. SrCrO 4 phase is a poor electrical conductor (1.8×10 -5 and 1.8×10 -4 S cm -1 at 700°C and 800°C respectively [41]). If it forms on the cathode, the SSCF cathode ohmic resistance will eventually increase.…”
Section: Interconnect Coating Effects On the Sscf Cathodementioning
confidence: 99%